Standardization of nitric oxide inhalation in extremely preterm infants in Japan. Issue 2 (26th February 2019) - Shiraishi, Jun; Kusuda, Satoshi; Cho, Kazutoshi; Nakao, Atsushi; Hiroma, Takehiko; Sugiura, Hiroshi; Suzuki, Satoshi; Oshiro, Makoto; Yoshimoto, Seiji; Watabe, Shinichi
Abstract: Background: In perinatal medicine, inhaled nitric oxide (iNO) has been an important tool for the treatment of full‐term and late‐preterm infants with persistent pulmonary hypertension of the newborn (PPHN) and hypoxemic respiratory failure (HRF). Its use in more premature infants, however, is controversial. To evaluate the current clinical practices regarding use of acute iNO in extremely preterm infants, a nationwide survey was conducted in Japan. Methods: A questionnaire survey was conducted from May to September, 2015. Questionnaires about PPHN and iNO treatment were sent to the doctor in charge of the neonatal care unit in 213 perinatal medical centers (PMC) that possessed iNO equipment in Japan. Results: A total of 143 of the 213 PMC provided responses (67.1%). A diagnosis of PPHN was made exclusively on echocardiography in all PMC. On definitive PPHN diagnosis, iNO was selected in the majority of the PMC (72%) and started from ≤10 p.p.m. in most PMC (49.7%) for extremely preterm infants. During iNO therapy, cardiac function was checked on echocardiography by a neonatologist every ≤8 h. iNO weaning was started when differential peripheral oxygen saturation (SpO2 ) disappeared, or when SpO2 reached 100% and so on. After iNO concentration reached 5 p.p.m., it was decreased gradually and carefully in five steps, taking 12–24 h to go from 5 to 0 p.p.m. Conclusions: Inhaled nitric oxide was predominantly used in extremely preterm infants as early rescue therapy for PPHN based on echocardiography performed by a neonatologist.